PERBANDINGAN KAPASITAS PEMASARAN MANGGA KE PASAR MODERN (KASUS DI KABUPATEN MAJALENGKA, INDRAMAYU DAN KUNINGAN) - Rasmikayati, Elly; Wiyono, Sulistyodewi Nur; Saefudin, Bobby Rachmat (Agros Journal of Agriculture Science, 2024)
The rapid growth of modern markets in Indonesia is an opportunity for farmers to expand the marketing of their farming businesses, including mango farmers. By marketing agricultural products in modern markets, farmers can increase their income, because the profits from selling mangoes in modern markets are greater than the profits from selling mangoes in traditional markets. However, in reality farmers still have difficulty penetrating the modern market. This phenomenon also occurs in mango farming in Indramayu, Majalengka and Kuningan Regencies. Based on this, this research aims to compare the marketing capacity of mangoes from Majalengka, Indramayu and Kuningan Regencies to modern markets. The method used in this research is a quantitative method with a questionnaire as an instrument in obtaining primary data, as well as the use of the Kruskal-Wallis method as a data analysis tool in this research. The research results show that overall, Indramayu Regency shows characteristics of more prosperous farmers and better marketing capacity compared to Majalengka and Kuningan. Majalengka Regency is superior in yield per tree and timing of harvest, while Kuningan has the best mango quality but lower marketing capacity than the other two districts. It is hoped that this research can provide a clear picture of the effectiveness of the marketing strategies implemented and the challenges faced by each district to increase their marketing capacity.Key-words: marketing capacity, modern market, mango farmers, mango farming